Math Practice Online > free > lessons > Florida > 9th grade > Two Variable Equations

These sample problems below for Two Variable Equations were generated by the MathScore.com engine.

## Sample Problems For Two Variable Equations

### Complexity=5, Mode=1

Solve for y and write the resulting equation beginning with 'y =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
 1.   17 = 5x + y 2.   5x = - 10y

### Complexity=10, Mode=1

Solve for y and write the resulting equation beginning with 'y =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
 1.   - 4y = 12x 2.   - 15 = - 4x + y

### Complexity=5, Mode=2

Solve for y and write the resulting equation beginning with 'y =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
 1.   - 10 = - 3x - 2y 2.   - 16 = 3x + 2y

### Complexity=10, Mode=2

Solve for x and write the resulting equation beginning with 'x =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
 1.   2x - 4y = - 13 2.   3x - 3y = - 19

### Complexity=5, Mode=3

Solve for y and write the resulting equation beginning with 'y =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
 1.   2y + 11 = - 10x + 3y 2.   - 3x - 8y = - 8y + 13

### Complexity=10, Mode=3

Solve for x and write the resulting equation beginning with 'x =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
 1.   - 3x + 6y = 4x + 18 2.   - 10y + 22 = 9x - 5y

### Complexity=5, Mode=1

Solve for y and write the resulting equation beginning with 'y =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
117 = 5x + y
Solution
17 - 5x = 5x + y - 5x
- 5x + 17 = y

y = - 5x + 17

25x = - 10y
Solution
Divide by - 10

### Complexity=10, Mode=1

Solve for y and write the resulting equation beginning with 'y =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
1- 4y = 12x
Solution
Divide by - 4

y = - 3x

2- 15 = - 4x + y
Solution
- 15 + 4x = - 4x + y + 4x
4x - 15 = y

y = 4x - 15

### Complexity=5, Mode=2

Solve for y and write the resulting equation beginning with 'y =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
1- 10 = - 3x - 2y
Solution
- 10 + 3x = - 3x - 2y + 3x
3x - 10 = - 2y

Divide by - 2

2- 16 = 3x + 2y
Solution
- 16 - 3x = 3x + 2y - 3x
- 3x - 16 = 2y

Divide by 2

### Complexity=10, Mode=2

Solve for x and write the resulting equation beginning with 'x =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
12x - 4y = - 13
Solution
2x - 4y + 4y = - 13 + 4y
2x = 4y - 13

Divide by 2

23x - 3y = - 19
Solution
3x - 3y + 3y = - 19 + 3y
3x = 3y - 19

Divide by 3

### Complexity=5, Mode=3

Solve for y and write the resulting equation beginning with 'y =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
12y + 11 = - 10x + 3y
Solution
2y + 11 - 11 = - 10x + 3y - 11
2y = - 10x + 3y - 11

2y - 3y = - 10x + 3y + - 11 - 3y
-y = - 10x - 11

Multiply by - 1
 -y(- 1) = (- 10x - 11)(- 1)

y = 10x - - 11

y = 10x + 11

2- 3x - 8y = - 8y + 13
Solution
- 3x - 8y + 3x = - 8y + 13 + 3x
- 8y = 3x - 8y + 13

- 8y + 8y = 3x + - 8y + 13 + 8y
0 = 3x + 13

### Complexity=10, Mode=3

Solve for x and write the resulting equation beginning with 'x =' and in simplified terms.
Examples: y = -x/5 + 12/5   x = 4y/3 - 2
1- 3x + 6y = 4x + 18
Solution
- 3x + 6y - 6y = 4x + 18 - 6y
- 3x = 4x - 6y + 18

- 3x - 4x = 4x + - 6y + 18 - 4x
- 7x = - 6y + 18

Divide by - 7

2- 10y + 22 = 9x - 5y
Solution
- 10y + 22 + 5y = 9x - 5y + 5y
- 5y + 22 = 9x

Divide by 9

MathScore.com

Copyright Accurate Learning Systems Corporation 2008.